Primary Pleural Benign Myxoid Schwannoma in an 18-Year-Old Female: A Case Report and Literature Review - Hussam Abou Al-Shaar; Safi Qutob; Ahmed Abu-Zaid; Ayman Azzam; Tarek Amin; Shamayel Mohammed (Case Reports in Oncological Medicine)
Pleural schwannomas are exceedingly rare neoplasms of the thoracic cavity. To the best of our knowledge, less than 20 cases have been reported in the medical English literature. Herein, we report the case of primary pleural benign myxoid schwannoma in an 18-year-old female. The patient was originally referred to our tertiary care hospital for further management of right adrenal gland mass. Physical examination and all laboratory tests were normal. Contrast-enhanced computed tomography scan showed a 4.2×3.2 cm, heterogeneous noncalcified mass involving the right adrenal gland region. The right renal vein and inferior vena cava were intact. There was no pleural effusion, ascites, or lymphadenopathy. No pelvic masses were identified. Patient was scheduled for surgical resection. On laparotomy, the mass was not found in its radiologically expected location, and the right kidney and right adrenal gland were intact. The right-sided lower part of diaphragm was opened, and the mass was interestingly found inside the thorax attached to the pleura, and resected successfully. A final histopathological diagnosis of primary pleural benign myxoid schwannoma was established. At a postoperative 6-month followup, there was no radiological evidence of tumor recurrence. Furthermore, literature review on pleural schwannomas is also presented.